2015
DOI: 10.5152/eurasianjmed.2015.0005
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Isotretinoin Treatment and Pregnancy: A Longitudinal Cohort Study from Turkey

Abstract: Objective: Isotretinoin is known to be the most effective treatment of severe and persistent acne. However, one of the most important adverse effects of this drug is known to be teratogenicity. In this regard, tests are administered before initiating the treatment, to assure that an unknown pregnancy is not present and accordingly, patients are advised to take contraceptive precautions during their systemic isotretinoin treatments. On the contrary, many cases of unwanted pregnancies and relevant abortuses have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 12 publications
(12 reference statements)
0
14
0
Order By: Relevance
“…Characteristics of the included studies are shown in Table 2 and summarized in Appendix B. (Chave et al, 2001;Mulryan et al, 2018) to 95.1% (Cheetham et al, 2006), pregnancy testing during treatment from 12.7% (Raguideau et al, 2015) to 100% (Hayward et al, 2016), contraception use before starting treatment from 15.7% (Uuskula et al, 2018) to 94% (Brandenburg et al, 2017), and contraception use during treatment from 1.7% (Tsur et al, 2008) to 100% (Ozyurt & Kaptanoglu, 2015).…”
Section: Risk Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Characteristics of the included studies are shown in Table 2 and summarized in Appendix B. (Chave et al, 2001;Mulryan et al, 2018) to 95.1% (Cheetham et al, 2006), pregnancy testing during treatment from 12.7% (Raguideau et al, 2015) to 100% (Hayward et al, 2016), contraception use before starting treatment from 15.7% (Uuskula et al, 2018) to 94% (Brandenburg et al, 2017), and contraception use during treatment from 1.7% (Tsur et al, 2008) to 100% (Ozyurt & Kaptanoglu, 2015).…”
Section: Risk Managementmentioning
confidence: 99%
“…B. Schwarz, Parisi, Williams, Shevchik, & Hess, 2012;E. B. Schwarz et al, 2007;Stancil et al, 2016;Steinkellner et al, 2010;Teichert et al, 2010;Uuskula et al, 2018;Wieck et al, 2007), while others used patients surveys (Algoblan et al, 2019;Banas et al, 2014;Bell et al, 2002;Boucher & Beaulac-Baillargeon, 2006;Brandenburg et al, 2017;Brinker et al, 2005;Castaneda et al, 2008;Chang et al, 2018;Ferguson et al, 2016;Goyal et al, 2015;Lelubre et al, 2018;Leverenz et al, 2019;Mitchell et al, 1995;Ozyurt & Kaptanoglu, 2015;Rao et al, 2000;E. B. Schwarz, Mattocks, et al, 2013;Shilalukey et al, 1997;Tsur et al, 2008;Valle et al, 1998;Werner et al, 2014;Yazdany et al, 2011), a combination of medical records and patient surveys (Bosak et al, 2019;Entezari-Maleki et al, 2012;Hogan et al, 1988;E.…”
Section: Risk Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…But on the contrary, many cases of unwanted pregnancies and relevant abortuses have been reported all over the world [18]. This indicates that there is still insufficient control of isotretinoin associated with pregnancy.…”
Section: Isotretinoinmentioning
confidence: 99%
“…Penicillins, macrolides, and cephalosporins are thought to have the best safety profile in pregnancy with erythromycin the oral antibiotic most commonly used for acne in pregnancy [18]. But tetracyclines should not be used during pregnancy, as use in the second and third trimester can cause discoloration of teeth and bones [20].…”
Section: Antibioticsmentioning
confidence: 99%